2012
DOI: 10.1007/s00213-012-2727-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in escalation of methamphetamine self-administration: cognitive and motivational consequences in rats

Abstract: Rationale Male rats escalate methamphetamine (meth) intake during long access meth self-administration, show enhanced reinstatement of meth seeking, and exhibit meth-induced memory impairments. However, the impact of long access daily meth self-administration on reinstatement and cognitive dysfunction has not been assessed in females, even though clinical studies on meth addiction have shown differences between men and women. Objectives This study determined whether male and freely-cycling female rats: 1) es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
147
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(178 citation statements)
references
References 46 publications
26
147
5
Order By: Relevance
“…What might account for our results showing no sex differences in methamphetamine selfadministration and relapse and the reported sex differences in the above-mentioned studies? Regarding methamphetamine self-administration, we suspect that the negative results in our study versus the positive results of sex differences in the previous studies (Reichel et al, 2012;Roth and Carroll, 2004) are due to the use of higher unit dose in our study than in these studies. Indeed, there is evidence that sex differences in cocaine and nicotine self-administration are more apparent when low drug doses are used (Carroll et al, 2001;Donny et al, 2000;Lynch and Carroll, 1999).…”
Section: Incubation Of Methamphetamine Craving After Voluntary or Forcontrasting
confidence: 57%
“…What might account for our results showing no sex differences in methamphetamine selfadministration and relapse and the reported sex differences in the above-mentioned studies? Regarding methamphetamine self-administration, we suspect that the negative results in our study versus the positive results of sex differences in the previous studies (Reichel et al, 2012;Roth and Carroll, 2004) are due to the use of higher unit dose in our study than in these studies. Indeed, there is evidence that sex differences in cocaine and nicotine self-administration are more apparent when low drug doses are used (Carroll et al, 2001;Donny et al, 2000;Lynch and Carroll, 1999).…”
Section: Incubation Of Methamphetamine Craving After Voluntary or Forcontrasting
confidence: 57%
“…The variation may be a result of inherent differences between males and females. Indeed, studies have identified meth self-administration differences between males and females (Reichel et al, 2012; Roth & Carroll, 2004). Future work programmatically examining possible sex differences in varenicline treatment of meth dependence would be needed to further elucidate the mechanism of these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, varenicline has been shown to partially substitute for the discriminative-stimulus effects of meth (Desai & Bergman, 2014). Additionally, the level of responding evoked by meth in a reinstatement test is sensitive to the dose (Anggadiradja et al, 2004; Reichel et al, 2012). The finding that 3.0 mg/kg varenicline had no effect may reflect a summative meth-like dose (i.e., varenicline + meth) that is on the descending portion of the meth-prime reinstatement curve.…”
Section: Discussionmentioning
confidence: 99%
“…Novel object recognition testing was performed as previously described (Reichel et al, 2012a). On abstinence day 7 or 14 (see Experimental Procedures), rats explored two identical objects for 3 min.…”
Section: Novel Object Recognitionmentioning
confidence: 99%
“…We hypothesized that such a model would engage the perirhinal cortex, which to date has not been implicated in relapse, despite its extensive interconnectivity with other brain regions, including the prefrontal cortex, nucleus accumbens, and amygdala (Kealy and Commins, 2011), all known to mediate relapse (Nawata et al, 2012;Rocha and Kalivas, 2010). Given that short-access meth rats do not exhibit deficits in novelty recognition (Reichel et al, 2012a;Rogers et al, 2008), and animals have an innate propensity to explore and interact with novel objects (Ennaceur and Delacour, 1988), we hypothesized that a novel cue would invigorate responding as well as a meth cue in short-access rats. In long-access rats, however, we anticipated that their deficits in novelty detection would bias them toward greater responding for the meth cue.…”
Section: Introductionmentioning
confidence: 99%